2018
DOI: 10.1186/s12986-018-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide, a gut microbiota-dependent metabolite of choline, is positively associated with the risk of primary liver cancer: a case-control study

Abstract: BackgroundEvidence has suggested a potential link exists between trimethylamine-N-oxide (TMAO), a choline-derived metabolite produced by gut microbiota, and some cancers, but little is known for primary liver cancer (PLC).MethodsA case-control study was designed including 671 newly diagnosed PLC patients and 671 control subjects frequency-matched by age (±5 years) and sex, in Guangdong province, China. High-performance liquid chromatography with online electrospray ionization tandem mass spectrometry (HPLC-MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…Isolated fasting serum samples were assessed using high-performance liquid chromatography with online electro-spray ionization tandem mass spectrometry to measure the concentrations of choline, and betaine. Detailed protocol of choline measurement has been described previously 19 . Detection of serum betaine was similar to choline, except for the internal standard was d9-betaine (obtained from Sigma-Aldrich, St. Louis, USA).…”
Section: Serum Choline and Betaine Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated fasting serum samples were assessed using high-performance liquid chromatography with online electro-spray ionization tandem mass spectrometry to measure the concentrations of choline, and betaine. Detailed protocol of choline measurement has been described previously 19 . Detection of serum betaine was similar to choline, except for the internal standard was d9-betaine (obtained from Sigma-Aldrich, St. Louis, USA).…”
Section: Serum Choline and Betaine Measurementmentioning
confidence: 99%
“…Experimental studies have reported that when deprived of choline, varying degrees of liver damages and liver diseases developed, including elevated transaminases 11 , affected lipid metabolism and transport 12 , fatty liver 13 , liver cirrhosis 13 and even liver cancer 14 , whereas choline or betaine supplementation ameliorated liver damage 15,16 , and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells 17 , which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline/betaine and human liver cancer risk, in which consistently favorable effects of choline were found. However, no existing studies have reported the associations between choline/betaine and liver cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“…Serum concentrations of choline and betaine were assessed by high-performance liquid chromatography with online electro-spray ionization tandem mass spectrometry to measure the concentrations of choline, and betaine. Detailed protocol of choline measurement has been described previously [19]. Detection of serum betaine was similar to choline, except for the internal standard was d9betaine (obtained from Sigma-Aldrich, St. Louis, USA).…”
Section: Serum Choline and Betaine Measurementmentioning
confidence: 99%
“…Experimental studies have reported that when deprived of choline, varying degrees of liver damage and liver diseases developed, including elevated transaminases [11], affected lipid metabolism and transport [12], fatty liver [13], liver cirrhosis [13] and even liver cancer [14], whereas choline or betaine supplementation ameliorated liver damage [15,16], and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells [17], which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline and betaine and human liver cancer risk, in which consistently favorable effects of choline were found. Of note, previous studies reported seriously insufficient dietary choline intake in Chinese population [20,21], and approximately 50% of the total HCC cases occurred in China [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation